Analysis of Total Coliform Bacteria in Domestic Wastewater of Makassar City Using the Most Probable Number (MPN) Method - Syaiful, Muhammad Fadhil; Amrullah, Syarif Hidayat; Amrullah, Dirhamzah; Anggraeni, Rini; Nurman; Rosmah (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
Domestic wastewater serves as a habitat for various microorganisms, including coliform bacteria. High concentrations of total coliform exceeding the established wastewater quality standards indicate the presence of pathogenic contaminants that may contribute to the spread of waterborne diseases. This study aimed to determine the total coliform bacteria present in domestic wastewater in Makassar City. The method used was microscopic examination employing the Most Probable Number (MPN) method. The results of the MPN test showed that out of 50 domestic wastewater samples analyzed, 29 samples (58%) met the wastewater quality standards, while 21 samples (42%) did not meet the established standards. The samples analyzed were collected from various sources of domestic wastewater, including hotels, hospitals, factories, and shopping centers distributed across Makassar City